2020
DOI: 10.1111/1471-0528.16089
|View full text |Cite
|
Sign up to set email alerts
|

An economic analysis of preimplantation genetic testing for aneuploidy by polar body biopsy in advanced maternal age

Abstract: Objective What are the cost per live birth and the incremental cost of preventing a miscarriage with preimplantation genetic testing for aneuploidy (PGT‐A) by polar body biopsy and array‐based comprehensive genome hybridisation (aCGH) versus regular IVF/ICSI without PGT‐A for infertility treatment in women 36–40 years of age? Design Decision tree model. Population A randomised clinical trial on PGT‐A (ESTEEM study). Methods Two treatment strategies were compared: one cycle of IVF/ICSI with or without PGT‐A. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The decision tree mode was modelled from the point of view of patients and does not take account of the costs incurred if a miscarriage occurs (relative risk PGT-A: 0.48) or the costs of a twin pregnancy (relative risk PGT-A: 0.54), which introduces bias against PGT-A. However, another cost analysis we carried out using four different international cost scenarios which took the costs of miscarriage into account also did not find that PGT-A was cost-effective [19]. A calculation of the incremental incurred cost of PGT-A to prevent a single miscarriage showed a cost dimension (at least € 73 434), which makes using PGT-A to reduce the rate of miscarriages unrealistic from an economic perspective.…”
Section: Discussionmentioning
confidence: 99%
“…The decision tree mode was modelled from the point of view of patients and does not take account of the costs incurred if a miscarriage occurs (relative risk PGT-A: 0.48) or the costs of a twin pregnancy (relative risk PGT-A: 0.54), which introduces bias against PGT-A. However, another cost analysis we carried out using four different international cost scenarios which took the costs of miscarriage into account also did not find that PGT-A was cost-effective [19]. A calculation of the incremental incurred cost of PGT-A to prevent a single miscarriage showed a cost dimension (at least € 73 434), which makes using PGT-A to reduce the rate of miscarriages unrealistic from an economic perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have failed to show improvements in live birth rates for women younger than 37 years of age [ 20–22 ], so it seems unlikely that the added complexity and cost of this intervention can be justified in younger patients. An economic analysis of preimplantation genetic testing for aneuploidy by polar body biopsy in woman of advanced maternal age showed that PGT-A greatly increased the cost and suggested that patients and doctors need to be aware of the high-cost implications of applying PGT-A [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have failed to nd improvement in live birth rates for women younger than 37 years of age [14] [15] [16], so it seems unlikely that the added complexity and cost of this intervention can be justi ed in younger patients. An economic analysis of preimplantation genetic testing for aneuploidy by polar body biopsy in advanced maternal age showed PGT-A increased the cost greatly and suggested patients and doctors need to be aware of the high-cost implications of applying PGT-A [17].…”
Section: Discussionmentioning
confidence: 99%